To Read and Learn: The Necessity for a New Definition of Dystopia and Bridging the Gap between the Old and Contemporary Dystopias Demir Alihodžić, and Selma Veseljević Jerković. The Boundaries of Dystopian Literature. The Genre in Context. OFF-SET d.o.o. - Pataki, Jelena (Anafora, 2023)
What is a dystopia? At first glance, this question seems quite easy to answer. The term, which has nowadays become extremely popular, especially among the young adult readership, is predominantly defined through its antonym and inevitable predecessor – utopia. Recognized as the negative counterpart of the utopia, that is, a perfectly organized, imagined society or place, dystopia is generally described as a bad place, or even more simply, a utopia gone wrong. Additionally, the dystopian world is inevitably linked to a totalitarian state apparatus, depriving its inhabitants of freedom by exercising strict control over all aspects of their lives. In this manner, terms such as negative or inverted utopia, and anti-utopia (7) are often used as its synonyms, making the entire affair seem simple enough.